Tinjauan Hukum Islam dan KUH Perdata terhadap Penyelesaian Wanprestasi Jual Beli Istishna di Toko Putra Jaya Tasikmalaya - Shifa Agnisa; Siska Lis Sulistiani; Iwan Permana (UNISBA Press, 2023)
Abstract. Implementation of goods buying and selling transactions with the Istishna system or what is called an order placed at the Putra Jaya Tasikmalaya Furniture Store, consumers are required to wait until the manufacturing process is complete to receive the goods depending on the size and level of difficulty of manufacture. The transaction system sometimes causes problems, where sellers cannot select buyers who have financial problems. Islamic religious teachings recommend always resolving buying and selling problems by way of deliberation, with the aim that both parties are pleased with each other and no one feels disadvantaged. The objectives to be achieved by researchers in this study include: (1) To find out the settlement of Istishna's sale and purchase default at the Putra Jaya Tasikmalaya Furniture Store according to Islamic law. (2) To find out the settlement of Istishna's sale and purchase default at the Putra Jaya Tasikmalaya Furniture Store according to KHUPerdata. The data analysis method used in this study is a normative juridical method, which means the method with an approach based on the main legal references with guidelines for studying theories, concepts, principles and laws and laws and regulations related to the theme of this research. The results of the analysis in the study show that the default made by the buyer is in the form of unilateral cancellation by the consumer because he cannot pay. The cancellation of a transaction contract unilaterally by the customer (shani') that occurred at the Putra Jaya Tasikmalaya furniture store is classified as an act that causes the transaction contract to be cancelled, causing losses to the seller, in this case the Putra Jaya Tasikmalaya furniture store. However, failure to pay in contract transactions is carried out when the goods have been made, this can also be justified because the buyer or customer has the right to refuse or the right of payment so that his party can choose to continue or cancel the sale and purchase contract if the order is not in accordance with what was done by the maker. Abstrak. Pelaksanaan transaksi penjualan barang dengan menggunakan sistem transaksi Istishna atau disebut dengan pesanan yang dilakukan pada Toko Putra Jaya Tasikmalaya, konsumen diharuskan menunggu hingga proses pembuatan selesai hingga menerima barangnya tergantung pada ukuran dan tingkat kesulitan pembuatan. Sistem transaksi tersebut kadang menyebabkan permasalahan, dimana penjual tidak dapat menyeleksi pembeli yang bermasalah dengan keuangan. Ajaran agama Islam menganjurkan untuk selalu menyelesaikan permasalahan jual beli dengan musyawarah, anjuran tersebut bertujuan agar kedua belah pihak saling menerima dan tidak ada satu pun yang merasa dirugikan. Tujuan yang ingin dicapai oleh peneliti ini diantaranya adalah: (1) Untuk mengetahui penyelesaian wanprestasi jual beli Istishna di Toko Putra Jaya Tasikmalaya menurut Hukum Islam. (2) Untuk mengetahui penyelesaian wanprestasi jual beli Istishna di Toko Putra Jaya Tasikmalaya menurut KHUPerdata. Metode analisis data yang digunakan dalam penelitian ini adalah metode yuridis normatif, yang artinya metode dengan pendekatan yang dilakukan berdasarkan referensi hukum utama dengan pedoman mempelajari teori, konsep, asas dan hukum serta peraturan perundang-undangan yang berkaitan dengan tema penelitian ini. Adapun hasil analisis pada penelitian menunjukan bahwa wanprestasi yang dilakukan dari pihak pembeli adalah berupa pembatalan secara sepihak dari konsumen karena tidak bisa membayar. Pembatalan akad transaksi secara sepihak oleh pemesan barang (shani’) yang terjadi di toko Putra Jaya Tasikmalaya tergolong perbuatan yang menyebabkan batalnya akad transaksi tersebut sehingga menimbulkan kerugian bagi pihak penjual yang dalam hal ini adalah pihak toko Putra Jaya Tasikmalaya.